On the compact modelling of Si nanowire and Si nanosheet MOSFETs. (5th January 2022) - Cerdeira, A; Estrada, M; Pavanello, M A
Abstract: In this paper, three-dimensional technology computer aided design simulations are used to show that the electron concentration, current density, and electric field distribution from the interface at the lateral channels and from the top channel to the centre of the silicon wire, in nanowire and nanosheet structures, are practically same. This characteristic makes it possible to consider that the total channel width for these structures is equal to the perimeter of the transistor sheet, allowing to extend of the application of the symmetric doped double-gate model (SDDGM) model to nanowires and nanosheets metal-oxide-semiconductor field effect transistors, with no need to include new parameters. The model SDDGM is validated for this application using several measured and simulated structures of nanowires and nanosheets transistors, with different aspect ratios of fin width and fin height, showing very good agreement between measured or simulated characteristics and modelled. SDDGM is encoded in Verilog-A language and implemented in the SmartSPICE circuit simulator.